Alexander The Great in Malay Literature: Analysis Descriptive - Adib Kurniawan (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The Hikayat Iskandar Zulkarnain is a significant literary work in the Malay tradition that transcends its role as a historical narrative to become a crucial medium for shaping and reinforcing political, cultural, and moral identities in Southeast Asia. This study explores the multifaceted impact of the Hikayat by analyzing its themes, narrative structure, and linguistic aspects. The text portrays Iskandar Zulkarnain (Alexander the Great) as the ideal ruler, embedding Islamic values and leadership qualities desired by Malay society. The narrative's structure, especially the Islamization episode in Habsyi, supports the depiction of divine guidance, making the Hikayat a didactic tool for instilling moral teachings. Linguistically, the text preserves archaic words that reflect the evolution of the Malay language, particularly in the Acehnese dialect, highlighting its importance as a cultural and historical document. Politically, the Hikayat has been used to legitimize the authority of Malay rulers by positioning Iskandar as a spiritual ancestor, thereby reinforcing their divine right to rule. Additionally, the narrative has been appropriated to construct national identities, especially in Aceh, where it was used to bolster the legitimacy of local rulers. Overall, the Hikayat Iskandar Zulkarnain remains a vital resource for understanding the interplay between literature, history, politics, and cultural identity in the Malay world.